PERBANDINGAN JUDICIAL REVIEW MAHKAMAH KONSTITUSI INDONESIA DENGAN GERMANY FEDERAL CONSTITUTIONAL COURT DAN IMPLIKASINYA SECARA GLOBAL - Muhammad Zaky (Transnasional, 2018)
The establishment of Constitutional Court is the answer to the development of constitutional law in countries in the world. It is an answer of needs for a new judicial institution. This expected new judicial institution does not only have to be independent. It has to be authorized to conduct interpretation the Constitution as well. Moreover, the Court should also be able to settle disputes between governmental agencies. In Indonesia, the set up of Constitutional Court of the Republic of Indonesia gives consequences to Indonesia’s state administration system in the 21st century. This shows particularly after the reformation era in Indonesia. Therefore, the Court itself is considerably new in Indonesia. It is also considered younger than the one in the other parts of the world, including the one in Germany. In terms of authority, the Germany Federal Constitutional Court has more limited authority than Constitutional Court of the Republic of Indonesia. However, Germany Federal Constitutional Court has a considerable legal power.